2016
DOI: 10.5539/mas.v10n8p75
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Effectiveness of Sternberg's Successful Intelligence Program on Executive Functions of Sharp-Witted Primary School Level Students

Abstract: The current research aimed to investigate the effectiveness of Sternberg's successful intelligence program on executive functions of sharp-witted primary school level students. The statistical universe of the current research consisted of all male sharp-witted students of the city of Isfahan in the educational year of 2015-2016. For this purpose, the number of 30 male sharp-witted students was selected through multi stage cluster random sampling method and was randomly placed in two experimental and control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Therefore, the observed ES was overestimated. Outlier analysis indicated that Malekopour et al's (2016) study ES was extremely high, g = 2.85, and thus considered an outlier. When the study was excluded from the analysis, the combined ES was g = 0.59, SE = 0.09, 95% CI [0.40, 0.78], which is within the range of average ES value.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, the observed ES was overestimated. Outlier analysis indicated that Malekopour et al's (2016) study ES was extremely high, g = 2.85, and thus considered an outlier. When the study was excluded from the analysis, the combined ES was g = 0.59, SE = 0.09, 95% CI [0.40, 0.78], which is within the range of average ES value.…”
Section: Resultsmentioning
confidence: 97%
“…Regardless of assessment types, students taught by TSI training outperform those educated by traditional teaching methods (Sternberg, Torff, & Grigorenko, 1998). TSI is usually applied in four ways: examining the relationship between triarchic abilities and academic achievement (Ekinci, 2014), assessing triarchic abilities for entry-level behavior in placement tests relative to scholastic aptitude tests (Stemler, Grigorenko, Jarvin, & Sternberg, 2006;Sternberg, 2006), implementing TSI techniques in psychotherapy training, and practice to aid depressed clients (Kaufman & Singer, 2003 (Malekpour, Shooshtari, Abedi, & Ghamarani, 2016) and academic hope-and reduces academic stress (Samavatian, Latifi, & Abedi, 2014). The principles of TSI have been applied to improve socioemotional outcomes such as motivation, attitude, and perception (Khakpooor, Abedi, & Manshaee, 2019;Zadeh, Abedi, Yousefi, & Aghababaei, 2014).…”
Section: Triarchic Instruction (Theory Of Successful Intelligence Training)mentioning
confidence: 99%
See 1 more Smart Citation
“…-L'importance de l' intelligence réussie À leur côté, (Malekpour et al, 2016) et (Macsinga et al, 2010) ont confirmé l'importance de la théorie de l'intelligence réussie car elle permet de (d'):…”
Section: La Flexibilitéunclassified